GAMBARAN TENTANG KOMPETENSI KEPRIBADIAN GURU PAUD KECAMATAN GAUNG ANAK SERKA KABUPATEN INDRAGIRI HILIR - alela, Sri; N, Zulkifli; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was conducted to find a picture of early childhood teachers personal competence district Gaung Anak Serka of Indragiri Hilir, whether the competence of the teacher's personality is good or not, so it can be seen how the competency of the teacher. The method used is descriptive survey with the technique of collecting data through questionnaires in the scale always, often, sometimes, never, distributed to 70 early childhood teachers district Gaung Anak Serka of Indragiri Hilir. The results showed personal competence early childhood teachers regency overall of indicators that are in either category, but when viewed from indicator there is one indicator that gets unfavorable category, even though the indicators are very important in personal competence due regard to the code of conduct of teachers. Thus, personal competence early childhood teachers must be addressed and improved in order to be better, because the competence of the teacher's personality is very important in shaping the character also influence the next generation.Keywords: Competence Personality